2009
DOI: 10.1590/s1983-32882009000200010
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of cortical thickness with magnetic resonance imaging in patients with bipolar disorder

Abstract: Changes in cortical thickness can be related to neuropsychiatric disorders and neurodegenerative processes. Previous studies have been conducted to characterize the pattern of changes in cortical thickness in several psychiatric diseases. The aim of the present study was to evaluate changes in cortical thickness with magnetic resonance imaging (MRI) in patients with bipolar disorder. Twenty-seven patients with bipolar disorder (14 male, 36.0 ± 16.2 years old; 13 female, 41.6 ± 10.7 years old) and 40 healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results showed that cortical thickness is a reliable quantitative feature for pattern classification [16]. Alzheimer's disease patients and normal people have also been studied through cortical thickness [17]. In a recent study, using the cortical thickness extracted based on SBM as a feature, this method determined 92% of cortical Feng et al BioMed Eng OnLine (2020) 19:13 lesions (sensitivity) and few false positives (96% specificity), thereby successfully distinguishing patients from normal people [13].…”
mentioning
confidence: 99%
“…The results showed that cortical thickness is a reliable quantitative feature for pattern classification [16]. Alzheimer's disease patients and normal people have also been studied through cortical thickness [17]. In a recent study, using the cortical thickness extracted based on SBM as a feature, this method determined 92% of cortical Feng et al BioMed Eng OnLine (2020) 19:13 lesions (sensitivity) and few false positives (96% specificity), thereby successfully distinguishing patients from normal people [13].…”
mentioning
confidence: 99%